2016
DOI: 10.1111/cpr.12276
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous polycaprolactone scaffolds with adhered platelets stimulate proliferation of skin cells

Abstract: Such complex stimulation is needed for improved healing of chronic wounds. However, the nanofibrous system can be used not only as a skin cover, but also in broader applications in regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 37 publications
3
24
1
Order By: Relevance
“…According to the data, PVA nanofibers are not suitable for cell culture regardless of their functionalization with platelets. The cell adhesion properties of PVA nanofibers could be improved using other polymers, such as chitosan [20], gelatin [21] or hyaluronic acid [22]. On the other hand, PCL was shown to be effective in fostering the culture of melanocyte, which is in accordance with previously published data [14,18].…”
Section: Discussionsupporting
confidence: 88%
“…According to the data, PVA nanofibers are not suitable for cell culture regardless of their functionalization with platelets. The cell adhesion properties of PVA nanofibers could be improved using other polymers, such as chitosan [20], gelatin [21] or hyaluronic acid [22]. On the other hand, PCL was shown to be effective in fostering the culture of melanocyte, which is in accordance with previously published data [14,18].…”
Section: Discussionsupporting
confidence: 88%
“…The performed SEM analysis demonstrated the presence of a fine fibrin network on the surface of the fibrous samples, functionalized with the highest concentrations of platelets. A similar fibrin network was observed in other studies, evaluating the positive effect of combining platelets and nanofibrous scaffolds [ 25 , 44 , 45 ]. It has been shown that the structure of the fibrin network, in terms of diameter, branching and density, may be influenced by various factors including pH and calcium, thrombin or fibrinogen concentration [ 46 ].…”
Section: Discussionsupporting
confidence: 85%
“…The best results were obtained in the centrifugally spun samples with the highest concentration of platelets (the highest tested concentration of platelet-derived molecules, C10). Nanofibers made of PCL, using electrospinning, were successfully used for the melanocyte culture [ 45 , 57 , 58 ]. Savkovic et al showed PCL nanofibers to be superior to a 2D cell culture substrate, in terms of melanin synthesis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emulsion of PF-68 in PCL reduced the surface tension of the polymeric solution and led to improved electrospinning efficiency. The needleless emulsion electrospinning resulted in the formation of nanofibres with nano−/micro-morphology typical for PCL electrospun from a chloroform/ethanol solvent system (Plencner et al, 2014;Vocetkova et al, 2016). The nano−/ micro-morphology was shown as a suitable morphology for the cultivation of chondrocytes (Jakubova et al, 2011) and fibroblasts (Plencner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%